2016
DOI: 10.1002/ana.24760
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral white matter lesions and post‐thrombolytic remote parenchymal hemorrhage

Abstract: Severe cerebral WMLs were associated with post-thrombolytic rPH but not with iPH within the ischemic area. Ann Neurol 2016;80:593-599.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
7
0
3
Order By: Relevance
“…In an observational study of 2,485 patients treated with alteplase, severe white matter lesions on CT, defined as a Blennow rating scale score of 5 or 6, was independently associated with remote parenchymal hemorrhage (adjusted OR 6.79, 95% CI: 2.57-17.94), but not with parenchymal hemorrhage strictly within the ischemic area (adjusted OR 1.45, 95% CI: 0.83-2.53). 205 Another study, based on MRI volumetric evaluations of white matter lesions, confirmed that larger whole brain corrected white matter lesion volume was associated with remote ICH, irrespective of the deep or periventricular location of white matter lesions. 206 PICO 13.6 In patients with acute ischaemic stroke of < 4.5 h duration, who have an unruptured cerebral aneurysm, does IVT with alteplase lead to better functional outcome than no IVT?…”
Section: Recommendationmentioning
confidence: 90%
“…In an observational study of 2,485 patients treated with alteplase, severe white matter lesions on CT, defined as a Blennow rating scale score of 5 or 6, was independently associated with remote parenchymal hemorrhage (adjusted OR 6.79, 95% CI: 2.57-17.94), but not with parenchymal hemorrhage strictly within the ischemic area (adjusted OR 1.45, 95% CI: 0.83-2.53). 205 Another study, based on MRI volumetric evaluations of white matter lesions, confirmed that larger whole brain corrected white matter lesion volume was associated with remote ICH, irrespective of the deep or periventricular location of white matter lesions. 206 PICO 13.6 In patients with acute ischaemic stroke of < 4.5 h duration, who have an unruptured cerebral aneurysm, does IVT with alteplase lead to better functional outcome than no IVT?…”
Section: Recommendationmentioning
confidence: 90%
“…Our results are in accordance with previous studies. One previous study suggested that the frequency of severe WMH increased the occurrence rate of rICH [12], and others emphasized the predictive value of severe WMH on AIS prognosis [6,21]. The mechanism that links greater WMH burden to a higher risk of rICH appears complex.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive leukoaraiosis has been associated with incident lobar hemorrhages in CAA patients [15]. In addition, a previous study showed that severe leukoaraiosis increased the risk of rPH [4]. Finally, a pathological study of 5 patients with ICH after thrombolytic therapy in myocardial infarction, showed that 3 of them had CAA [16].…”
Section: Discussionmentioning
confidence: 99%
“…This type of ICH occurs in 1.3–3.7% of patients within 24–36 hours after the infusion of IV-rtPA but risk factors are not well-known [24]. It is likely that IV-rtPA triggers rPH when there is an underlying hemorrhagic-prone cerebral angiopathy, such as hypertensive and amyloid angiopathies [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation